2005
DOI: 10.1039/b417832g
|View full text |Cite
|
Sign up to set email alerts
|

A simple cobalt catalyst system for the efficient and regioselective cyclotrimerisation of alkynes

Abstract: The intermolecular cyclotrimerisation of terminal and internal alkynes can be catalysed by simple cobalt complexes such as a CoBr2(diimine) under mild reaction conditions when treated with zinc and zinc iodide with high regioselectivity in excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
61
1
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(66 citation statements)
references
References 23 publications
(1 reference statement)
1
61
1
2
Order By: Relevance
“…In this context it should be noted that hexaphenyl benzene displays only a single multiplet in its 1 H NMR spectrum at d = 6.83 ppm. [21] The assignments made here for the new derivatives 8-15 were aided by heteronuclear CH COSY (HMQC) spectra and the clear observation of vicinal coupling in homonuclear HH COSY (TOCSY) experiments between H7 and H10 and between H8 and H11. HMBC NMR experiments were used to determine the 13 C NMR signals of the quaternary carbons C13, C14, and C15 and the aromatic protons H8 and H11 by virtue of their coupling (see Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…In this context it should be noted that hexaphenyl benzene displays only a single multiplet in its 1 H NMR spectrum at d = 6.83 ppm. [21] The assignments made here for the new derivatives 8-15 were aided by heteronuclear CH COSY (HMQC) spectra and the clear observation of vicinal coupling in homonuclear HH COSY (TOCSY) experiments between H7 and H10 and between H8 and H11. HMBC NMR experiments were used to determine the 13 C NMR signals of the quaternary carbons C13, C14, and C15 and the aromatic protons H8 and H11 by virtue of their coupling (see Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…We can not rationalize the effect of the iron powder in preventing the formation of the [2+2+2]-cyclotrimerization side product. [8] When one component of the catalyst system is omitted, reduced chemoselectivities or reduced conversions are encountered. In some cases the formation of the 1,3,6-cyclooctatriene side product is observed.…”
mentioning
confidence: 99%
“…A recent theoretical study [12] showed that the flyover (C 6 R 6 ) Co 2 (CO) 4 compounds are the lowest energy structures only for systems with large R groups such as those with multiple CF 3 and/or tert-butyl substituents. For systems with smaller R groups, including (C 6 H 6 )Co 2 (CO) 4 and (C 6 Me 6 )Co 2 (CO) 4 , isomeric structures with a bent benzene ring bridging the two cobalt atoms were found to be lower energy structures than the corresponding ''flyover'' compounds ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Such complexes have been isolated and characterized structurally in systems with large R substituents, e.g. [1,3,6-tBu 3 C 6 H 3 ]Co 2 (CO) 4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation